Education and Scientific Initiation in the pandemic: analyzing remote studies of elementary school - Daniel Giordani Vasques; Victor Hugo Nedel Oliveira (Universidade Federal do Oeste da Bahia, 2021)
The COVID-19 pandemic changed several practices, including educational ones. The main objective of this investigation was to analyze the systematization of home studies of the discipline "Projeto Amora", related to Scientific Initiation, at the UFRGS Application College. To this end, a case study and documentary analysis of the activities of the 6th and 7th years of elementary school were carried out, with a corpus composed of 19 works analyzed from elements related to resources, type of activity, reflections and content. Results showed that the most used resource was "text" and that the type of activity that most occurred were essay questions. The reflections requested in greater evidence refer to the experiences during the quarantine. And, finally, the contents that most occurred were related to the instrumentalization of students for the new pedagogical model established. It is possible to consider that the pedagogical interests of this component are associated with work limitations in times of pandemic.